Nuclear Mechanics: Nuclear Mechanics within Intact Cells Is Regulated by Cytoskeletal Network and Internal Nanostructures (Small 18/2020). Issue 18 (7th May 2020) - Zhang, Jitao; Alisafaei, Farid; Nikolić, Miloš; Nou, Xuefei A.; Kim, Hanyoup; Shenoy, Vivek B.; Scarcelli, Giuliano
Abstract : In article number 1907688, Vivek B. Shenoy, Giuliano Scarcelli, and co‐workers use all‐optical Brillouin microscopy and 3D chemomechanical modeling to investigate the regulation of nuclear mechanics. It is observed that the nuclear modulus can be modulated by both epigenetic regulation targeting internal nanostructures and cytoskeletal behavior through a robust mechanism conserved in different culturing conditions.